A new species of Wolf Snake of the genus Lycodon H. Boie in Fitzinger (Squamata: Colubridae) from the Aceh Province of northern Sumatra, Indonesia - Wostl, Elijah; Hamidy, Amir; Kurniawan, Nia; Smith, Eric N. (Zootaxa, 2017)
Herein we describe a new species of Lycodon H. Boie in Fitzinger (Squamata: Colubridae) from Aceh Province, Sumatra. This brings the number of species known to occur on the Sunda Shelf to seven. The new species is readily diagnosed from the other congeners in the region by the lack of a preocular scale, the presence of keeled dorsal scales and a banded venter. It is superficially similar to L. butleri from the Malaysian Peninsula in coloration and to L. subcinctus in head scalation. Genetically, the new species is most similar to a group of species from Mainland Southeast Asia and China. We also note the presence of several deeply divergent lineages within Lycodon that may warrant the recognition as distinct genera. The genus is in need of a comprehensive molecular and morphological review.